Characterization and Explanation of the Destination Choice Patterns of Canadian Male Labour Force Entrants 1971-76 - Moffett, Patricia (My University, 1984)
Since the classic study of migration and metropolitan growth by Lowry (1966), migration researchers have assumed a two-stage process wherein the decision to migrate is followed by the destination choice decision. Such an approach is employed here, to provide a characterization and explanation of the destination choice patterns of the male labour force entrants.
Specifically, a nonlinear migration model, developed by Liaw and Bartels (1982), is applied to Canadian migration data for the 1971-76 period. The inter-metropolitan migration patterns of the male labour force entrants is found to be well explained by six explanatory variables: population size, logarithmic distance, housing growth, employment increase, cultural barriers and "strong ties". The last two variables are dummy variables derived from the characterization of the destination choice patterns through the application of entropies. The study examines factors involved in the destination choice decision and concludes with suggestions for future investigation.
Keywords: characterization, explanation, choice patterns, destination, Canadian, male labour, force, migration model